The construction of resveratrol-loaded protein–polysaccharide–tea saponin complex nanoparticles for controlling physicochemical stability and in vitro digestion. Issue 11 (29th October 2020) - Wei, Yang; Li, Chang; Dai, Lei; Zhang, Liang; Liu, Jinfang; Mao, Like; Yuan, Fang; Gao, Yanxiang
Abstract : The novel zein–propylene glycol alginate (PGA)–tea saponin (TS) ternary complex nanoparticles were fabricated to deliver resveratrol. Abstract : The novel zein–propylene glycol alginate (PGA) –tea saponin (TS) ternary complex nanoparticles were fabricated to deliver resveratrol. TS was firstly introduced to modulate the functional attributes, microstructure, molecular interactions and gastrointestinal digestion of the complex nanoparticles. The size of zein–PGA–TS complex nanoparticles was between 281.9 and 309.7 nm. In the presence of TS, the encapsulation efficiency of resveratrol was significantly elevated from 58.43% to 85.58%. The environmental stability of resveratrol was improved through entrapping into the complex nanoparticles with the rise in TS proportion. Multiple spectroscopic methods revealed that TS altered the micro-environment and secondary structure of the protein. Hydrogen bonds, hydrophobic effects and electrostatic interactions contributed to the formation of complex nanoparticles. Differential scanning calorimetry (DSC) and X-ray diffraction (XRD) patterns showed the amorphous nature of the encapsulated resveratrol. Field emission scanning electron microscopy (FE-SEM) confirmed the globular shape of the nanoparticles and their different aggregation states were dependent on the particle compositions. Moreover, the zein–PGA–TS complex nanoparticles exhibited the best sustained release in the small intestine when the mass ratio of zein to TS was 5 : 1 (23.20% in the stomach and 63.11% in the small intestine). These findings indicated the influence of TS on the properties and applications of the protein–polysaccharide complexes, which provided a new insight into the development of novel food grade nanoparticles with desirable stability and digestion behaviour.